Analisis Mekanisme Sumber Gempa Mikro di Lapangan Panas Bumi Wayang Windu, Kecamatan Pangalengan, Kabupaten Bandung, Jawa Barat untuk Prediksi Zona Permeabilitas - Rhamadhana Sultan; Sulaehani Ruhmi (Mataram University, 2026)
Microearthquakes in producing geothermal fields, such as the Wayang Windu geothermal field, are valuable for monitoring subsurface and reservoir conditions. This study analyzes micro seismic data recorded by seismometer stations to determine focal mechanisms and fault orientations, aiming to predict permeability zones. Moment tensor inversion was performed using the ISOLA program (MATLAB-GUI), applying a linear least-squares method based on Green’s functions and P-wave arrival times from three-component seismometers. Reliable inversion results are indicated by variance reduction values approaching unity. The results reveal both double-couple (DC) and non-DC components, including Compensated Linear Vector Dipole (CLVD) mechanisms. Non-DC sources are associated with fluid injection and increased pore pressure, while DC components indicate shear faulting. Focal mechanism solutions (beach ball diagrams) show that faults in the production area are predominantly oblique, with dips ranging from 30° to 90°, whereas the injection area is dominated by reverse faults with dips of 20° to 85°. These findings suggest that permeability zones are present in both production and injection areas, as supported by hypocenter distribution and fault orientations. Fluid movement is interpreted to trend northward, with permeability enhancement linked to fluid injection that elevates pore pressure and promotes fracture opening.